(untitled) - Mandelbaum, K. (Oxford, 1955)
The implications —income distribution among various classes, rates of growth of the various categories of industry, capital requirements for each, etc.—are worked out in considerable detail. In a sense the detailed figures are mere guesses, but they are based on good analogies, and there is an element of double entry present which serves as check. The work is scholarly, and in its quantitative aspect authoritative. Human, social and political difficulties are admittedly neglected.
Keywords: Công nghiệp hóa,Industrialization